2017
DOI: 10.17755/esosder.327488
|View full text |Cite
|
Sign up to set email alerts
|

Seçi̇m Kuramina Dayali Psi̇koeği̇ti̇m Programinin Ergenleri̇n Ri̇skli̇ Davranişlari Ve İyi̇li̇k Hali̇ Üzeri̇ndeki̇ Etki̇si̇ni̇n İncelenmesi̇

Abstract: Bu araştırmanın amacı seçim kuramı ve gerçeklik terapisine dayalı psikoeğitim programının ergenlerin riskli davranışları ve iyilik hali düzeyleri üzerindeki etkisini incelemektir. Araştırma, Aydın ilindeki bir Mesleki ve Teknik Anadolu Lisesi'nde öğrenim gören riskli davranışlara sahip ergenler ile yürütülmüştür. Deney, karşılaştırma ve kontrol gruplarının her birinde 15'er öğrenci olmak üzere araştırmada toplamda 45 öğrenci yer almıştır. Öğrenciler deney, karşılaştırma ve kontrol gruplarına seçkisiz olarak at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…When the results of these studies are evaluated in general, it is seen that intervention programs have been effective in reducing the experimental group participants' level of cyberbullying (Tanrıkulu, 2013), school dropout, antisocial behaviors (Erbaş & Kağnıcı, 2017); academic procrastination tendency (Berber Çelik & Odacı, 2018) and health score of "somatic symptoms, anxiety, social dysfunction, depression" (Pourzangiabadi et al, 2020), problematic internet use (Dursun, 2020); and in increasing their level of obtaining information, evaluating information, triggering change, seeking options, creating a plan, implementing a plan, the effectiveness of the plan and self-regulation (Hajhosseini et al, 2016), responsibility (Vaziri et al, 2014) and resilience, and internal locus of control (Ünüvar, 2012). In other words, group intervention programs developed based on reality therapy were found to have a significant effect on the experimental groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the results of these studies are evaluated in general, it is seen that intervention programs have been effective in reducing the experimental group participants' level of cyberbullying (Tanrıkulu, 2013), school dropout, antisocial behaviors (Erbaş & Kağnıcı, 2017); academic procrastination tendency (Berber Çelik & Odacı, 2018) and health score of "somatic symptoms, anxiety, social dysfunction, depression" (Pourzangiabadi et al, 2020), problematic internet use (Dursun, 2020); and in increasing their level of obtaining information, evaluating information, triggering change, seeking options, creating a plan, implementing a plan, the effectiveness of the plan and self-regulation (Hajhosseini et al, 2016), responsibility (Vaziri et al, 2014) and resilience, and internal locus of control (Ünüvar, 2012). In other words, group intervention programs developed based on reality therapy were found to have a significant effect on the experimental groups.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of the meta-analysis of twenty-one reality therapy-based studies, it was concluded that there was a moderate level of effectiveness (Radtke, Sapp, and Farrell, 1997: 5). In almost all of the studies examined, quantitative measurement tools are seen to be preferred to measure the effectiveness of the program (Berber Çelik and Odacı, 2018;Erbaş & Kağnıcı, 2017;Hajhosseini et al, 2016;Pourzangiabadi, 2020;Vaziri et al, 2014). In addition to the quantitative measurement tools, preferring qualitative measurement tools can be seen as important in order to deeper understand the effectiveness of the program and the experiences of the participants during the program process.…”
Section: Discussionmentioning
confidence: 99%
“…Alanyazında önleme programlarının problem davranışları azalttığına yönelik meta-analitik olarak incelenen çalışmalar yer almaktadır (Durlak ve Wells, 1998;Wilson vd., 2001). Farklı problem davranışların önlenmesinde, beceri kazanımına yönelik psikoeğitim programının etkili olduğu ve bu etkinin kalıcı olduğuna dönük araştırmalara alanyazında rastlanmaktadır (Erbaş, 2017;Mutiso vd., 2017). Bir problem davranışa sahip ergenin, bir diğer problem davranışa da sahip olma olasılığı yüksektir (Jessor, 2016).…”
Section: Tartışma Ve Sonuçunclassified